Development of Rtb (Rescue The Ball) Game Models for Physical Education Learning Soccer Games - Bayu Hardiyono; Aprizal Fikri; I Bagus Endrawan; Ranto Manullang (Universitas PGRI Palembang, 2023)
Improving the quality of education is a national education goal and is an integral part of efforts to improve the quality of Indonesian students as a whole. All children have the right to get education and learn according to their rights, of course not all also in schools get adequate facilities because of the lack of infrastructure, especially at the field of sports in physical education learning. Each Student used improvised infrastructure from the school which makes students in physical education lessons limited abd tends to be monotounsin physical education subjects. Therefore the purpose of this research is to develop an RTB (Rescue The Ball) game model for learning physical education, soccer game desaigned to make students move actively and make learning physical education fun. This development involves 3 experts, namely physical education experts, game experts, and soccer experts. The method used Research Borg and Gall Research and Development (R&D) The results of the validation test by experts using the content validity index (CVI) and content Validity Ratio (CVR) test which show and average CVR value of 0,8 in other words of RTB (Rescue The Ball) Development model is appropriate or relevant, or good and also has high content validity in improving basic technical. RTB (Rescue The Ball) game model for physical education learning soccer games, this game is feasible to continue in elementary schools as a follow-up recommendation from this research. RTB is an alternative for elementary school physical education teachers when they want to teach soccer material. It is unique because it combines traditional games and soccer using a field that is not too wide.